PENGARUH SIFAT MATERIALISME, MOTIVASI HEDONIK TERHADAP IMPULSIVE BUYING DAN KECENDERUNGAN COMPULSIVE BUYING SECARA ONLINE DI KALANGAN MAHASISWA UNIVERSITAS MATARAM - Rini Anggriani; Handry Sudiartha Athar (Master of Management, Mataram University, 2017)
This reasearch is aimed at determining the effect of materialism, hedonistic motive on the online impulsive buying and compulsive buying trend in students of Mataram University. This research is causality study using purposive sampling. The populations are all students of Mataram University and the samples are 120 selected students who have made online transaction purchasing fashion at least twice within the last three months. The data were analyzed with Structural Equation Modeling (SEM).The research showed that variable of materialism has positive and significant effect on the impulsive buying. The materialism also has positive and significant effect on the compulsive buying trend. Hedonistic motive has positive and significant effect on the compulsive buying trend. There is no effect of the impulsive buying on the online compulsive buying trend in the students of Mataram University. Key words: Materialism, Hedonistic Motive, Impulsive Buying, Compulsive Buying Trend.